Mechanistic Insights into Performance and Stability Enhancement of Infiltrated Solid Oxide Electrochemical Cell Electrodes - Lee, Jinsil; Park, Jinhong; Kim, Taeyun; Choi, Soomin; Kim, Seong Kyun; Yoon, Kyung Joong; Joo, Jong Hoon (Wiley - V C H Verlag GmbbH & Co., 2025)
Surface modification via nanocatalyst infiltration has emerged as an effective strategy for enhancing the performance and lifespan of high-temperature electrochemical devices, addressing the limitations of conventional perovskite-based air electrodes. Although surface modification has been widely adopted, how infiltration simultaneously enhances electrochemical activity and durability remains unclear. Herein, the effect of Sm0.5Sr0.5CoO3-delta (SSC) infiltration into La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF) electrodes is systematically investigated using dense model systems, which enable for detailed analysis of surface phenomena and accurate quantification of electrochemical processes. The SSC coating significantly enhanced the oxygen surface-exchange kinetics while concurrently suppressing cation segregation and phase decomposition under the solid oxide fuel cell (SOFC) operating conditions. This improvement is attributed to the reduced electrode polarization via the catalytic promotion of surface reactions, which lowers the surface potential and mitigates instability in the LSCF backbone. These findings are consistently validated in full-cell configurations, confirming that infiltration not only improved performance but also suppressed Cr poisoning and phase decomposition. This study offers new insights into the dual role of infiltration in enhancing both the catalytic activity and structural stability, establishing design principles for durable, high-performance SOFC electrodes.